Homeobox B9 Mediates Resistance to Anti-VEGF Therapy in Colorectal Cancer Patients - Carbone, Carmine; Piro, Geny; Simionato, Francesca; Ligorio, Francesca; Cremolini, Chiara; Loupakis, Fotios; Alì, Greta; Rossini, Daniele; Merz, Valeria; Santoro, Raffaela; Zecchetto, Camilla; Zanotto, Marco; et al. (Clinical cancer research, 2017)
The identification of predictive biomarkers for antiangiogenic therapies remains an unmeet need. We hypothesized that the transcription factor Homeobox B9 (HOXB9) could be responsible for the tumor resistance to the anti-VEGF agent bevacizumab. HOXB9 expression and activation were measured in eight models of colorectal and pancreatic cancer with different resistance to bevacizumab. Serum levels of Angiopoietin-like Protein (Angptl)2, CXC receptor ligand (CXCL)1, IL8, and TGFβ1 in tumor-bearing mice were measured by multiplex xMAP technology. HOXB9 expression was measured by immunohistochemical analysis in 81 pretreatment specimens from metastatic colorectal cancer patients. Differences in progression-free survival (PFS) were determined using a log-rank test. HOXB9-positive tumors were resistant to bevacizumab, whereas mice bearing HOXB9-negative tumors were cured by this agent. Silencing HOXB9 in bevacizumab-resistant models significantly ( < 0.05) reduced Angptl2, CXCL1, IL8, and TGFβ1 levels, reverted their mesenchymal phenotype, reduced CD11b+ cells infiltration, and restored, in turn, sensitivity to bevacizumab. HOXB9 had no prognostic value in patients treated with a first-line chemotherapeutic regimen noncontaining bevacizumab. However, patients affected by an HOXB9-negative tumor had a significantly longer PFS compared with those with an HOXB9-positive tumor if treated with a first-line regimen containing bevacizumab (18.0 months vs. 10.4 months; HR 2.037; 95% confidence interval, 1.006-4.125; = 0.048). These findings integrate the complexity of numerous mechanisms of anti-VEGF resistance into the single transcription factor HOXB9. Silencing HOXB9 could be a promising approach to modulate this resistance. Our results candidate HOXB9 as predictive biomarker for selecting colorectal cancer patients for antiangiogenic therapy. .